Harnessing the Gains of Socio-constructive Strategy for Learning in Nigerian Primary Schools in the Post Covid Era: Implication for National Development (2023)
The covid-19 pandemic shutdown systems and institutions globally, the period did not leave out any organisations; as schools at all levels were shut down for several months. Educationists have therefore, been looking for solutions to resume back to school life and possibly put structures in place for future unfavourable situations which could lead to school closure and find teaching strategy which will be able to withstand the effect of the pandemic on pupils at the basic level of education. Therefore, this study showcases the gains of social constructive learning strategy in Nigeria primary schools post COVID-19. Two research questions were raised and answered while two hypotheses were tested at 0.05 level of significance while mixed method research design was adopted. Results of the study reveal learning loss, poor academic performance and neglect of rural schools during the COVID-19 pandemic. Results of the intervention show that Social constructive learning strategies makes learning effective, children could interact during learning, teamwork, empathy and communication skills were also developed during the intervention. It was recommended that more teachers should be trained on the use of social constructive learning strategy, parents and policy experts should also create supportive environment for social constructive learning strategy.